The role of endoscopic lung volume reduction in the treatment of emphysema [Amfizem tedavisinde endoskopik akciger hacim küçültme isleminin rolü] - (:unkn) unknown (My University, 2011)
Chronic obstructive pulmonary disease is a group of lung diseases characterized by chronic airflow obstruction and hyperinflation. Evidence-based reviews of management approaches, providing stepped-care algorithms for pharmacological and non-pharmacological therapy have been published. In the last decades, many studies were conducted in order to design additional non-pharmacologic approaches, especially for patients with emphysema. Clinical studies performed with three different endoscopic lung volume reduction techniques have shown promising data and reached later stage clinical trials in patients with heterogeneous emphysematous diseases. These three techniques include reversible airway blocking techniques, reversible non-blocking techniques and irreversible non-blocking techniques. For homogeneous disease the formation of airway bypass tracts is being investigated. The aim of this article is to give an overview of the techniques and the available data.
Keywords: Endoscopic lung volume reduction; Forced expiratory volume; Lung diseases/obstructive/therapy